Circulating plasma levels of follicle-stimulating hormone, luteinizing hormone and testosterone in malnourished male children - Nduka, Ebere U.; Dada, Olukayode A.; Johnson, Abiodun O.; Agbedana, E. Oluyemi (The Turkish Journal of Pediatrics, 1987)
The effect of protein-energy malnutrition on the pituitary-gonadal axis was examined and discussed. In the seventeen cases of malnutrition, eight were of the kwashiorkor type while nine were of the marasmic type. Although it was found that the mean LH levels in the children with marasmus were higher (p < 0.002) than in both the controls and the kwashiorkor patients, and the mean FSH levels in both the marasmus subjects and the controls were significantly higher (p < 0.02) than that obtained in the kwashiorkor patients, the mean testosterone levels were significantly lower (p < 0.01) in those with kwashiorkor than in the marasmus or the control subjects. The results obtained from this study suggest that protein-energy malnutrition in children may induce some changes in the endocrine status or it may lead to an impairment in pituitary gonadal axis function. These changes are apparently more extreme in kwashiorkor than in marasmus.
Keywords: follicle-stimulating hormone; luteinizing hormone; testosterone; malnourished children